2018
DOI: 10.1002/sia.6542
|View full text |Cite
|
Sign up to set email alerts
|

Study on carbon dioxide reduction with water over metal oxide photocatalysts

Abstract: Various metal oxides with 0.1 wt% Ag loaded as a cocatalyst were prepared by an impregnation method and examined their photocatalytic activity for CO2 reduction with water. Among all the prepared Ag‐loaded metal oxides, Ga2O3, ZrO2, Y2O3, MgO, and La2O3 showed activities for CO and H2 productions under ultraviolet light irradiation. Thus, metal oxides involving metal cations with closed shell electronic structures such as d0, d10, and s0 had the potential for CO2 reduction with water. In situ Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition, Ga 2 O 3 consisting of two phases, α- and γ-phases or β- and γ-phases, shows the photocatalytic activity for CO 2 reduction, for which their phase boundaries are reported to be active sites for CO 2 reduction. Precipitation of gallium oxide hydroxide (GaOOH) on α- and β-phases is also reported to increase the photocatalytic CO 2 reduction . In most cases, noble metals such as Ag and Pt have been employed as cocatalysts to enhance CO productivity in photocatalytic CO 2 reduction. However, it has been reported that without a cocatalyst, Ga 2 O 3 consisting of two phases, α- and β- or β- and γ-phases, exhibits high activity for the photocatalytic CO 2 reduction. ,, It should be noted that except for the β-phase, no single phase of Ga 2 O 3 is examined as a photocatalyst for CO 2 reduction with water because of the lack of thermal stability and difficulties in their synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ga 2 O 3 consisting of two phases, α- and γ-phases or β- and γ-phases, shows the photocatalytic activity for CO 2 reduction, for which their phase boundaries are reported to be active sites for CO 2 reduction. Precipitation of gallium oxide hydroxide (GaOOH) on α- and β-phases is also reported to increase the photocatalytic CO 2 reduction . In most cases, noble metals such as Ag and Pt have been employed as cocatalysts to enhance CO productivity in photocatalytic CO 2 reduction. However, it has been reported that without a cocatalyst, Ga 2 O 3 consisting of two phases, α- and β- or β- and γ-phases, exhibits high activity for the photocatalytic CO 2 reduction. ,, It should be noted that except for the β-phase, no single phase of Ga 2 O 3 is examined as a photocatalyst for CO 2 reduction with water because of the lack of thermal stability and difficulties in their synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the recycling of CO 2 into low-carbon chemicals or fuels using solar energy is considered an economically attractive and environmentally friendly route. The desired photocatalysts for the photocatalytic reduction of CO 2 to chemicals or fuels under mild conditions are being developed to achieve the goal of CO 2 recycling [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the absorption band at ∼1557 cm −1 was attributed to the COOH* group, 20 one of the most common intermediates during photocatalytic CO 2 reduction process. The peak at 1320 cm −1 was attributed to the b-CO 3 2− * group, 21,22 which originated from CO 2 dissolving in H 2 O. Importantly, the peaks at 1064 and 1020 cm −1 may correspond to the *CH 3 O and *CHO groups, 7 both of which were the key intermediates for photocatalytic CO 2 reduction toward CH 4 production.…”
mentioning
confidence: 99%